Sustainability and Innovation Practices in Leather and Footwear Industry: A Systematic content Analysis (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The goal of sustainability is to satisfy current  needs without jeopardizing the ability of future  generations to satisfy their own demands. In  the leather and footwear sectors, sustainability  is defined as shoe design, development,  manufacturing, distribution, and selling  procedures that reduce the negative effects on  the environment, conserve energy and natural  resources, are secure for workers, communities,  and customers, and are financially prudent. In  this study, the scientific literature on innovation  and sustainability in the footwear sector during  the previous ten years will be analyzed. The  study is in the descriptive and exploratory  categories. The procedure produced 38 papers  in the Scopus database and Google Scholar  that matched the research topic. From 2000 to  2023, on the subject of leather and footwear,  the bibliometric analysis identified the most  pertinent papers, authors, keywords, nations,  research institutions, and journals. For the  purpose of bibliometric analysis, R Studio will be  used. The leather and footwear industries must  support each other in terms of innovation and  sustainability, which we tried to find through a  systematic literature review analysis. Innovation  in the footwear industry is an important factor,  and due to the reduction of raw materials such as  leather and the negative impact of leather on the  environment, the importance of sustainability  in the footwear industry has increased.
Keywords: Sustainability; Innovation; Bibliometric analysis; Leather and Footwear Industry